2014
DOI: 10.4236/ojim.2014.43015
|View full text |Cite
|
Sign up to set email alerts
|

HEALS: A Faith-Based Hypertension Control Program for African-Americans: A Feasibility Study

Abstract: Objective: To determine the feasibility of a behavioral faith-based PREMIER study modified hypertension (HTN) control intervention in a semi urban African-American (AA) church. Methods: In a prospective longitudinal study design, a 12-week behavioral HEALS (Healthy Eating and Living Spiritually) intervention was tested for its feasibility and efficacy in a semi urban AA church. High-risk adult church members with HTN were recruited. Program sessions were weekly delivered by the trained church members. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Details on HEALS program development are published elsewhere [20][21][22][23]. Briefly, with the input from the CAB, academic experts, and Christian church pastors, the 12-week HEALS intervention sessions were developed and modified from the 18week PREMIER lifestyle program (including DASH diets) into a multi-level, culturally tailored, faith-based, and faith-placed group intervention (Table 1), theoretically grounded in the Social Cognitive Theory [24][25][26].…”
Section: Heals Interventionmentioning
confidence: 99%
“…Details on HEALS program development are published elsewhere [20][21][22][23]. Briefly, with the input from the CAB, academic experts, and Christian church pastors, the 12-week HEALS intervention sessions were developed and modified from the 18week PREMIER lifestyle program (including DASH diets) into a multi-level, culturally tailored, faith-based, and faith-placed group intervention (Table 1), theoretically grounded in the Social Cognitive Theory [24][25][26].…”
Section: Heals Interventionmentioning
confidence: 99%
“…A 10-hr training workshop for CHAs on CHHIL and HEALS (parents' lifestyle program) was conducted by the research team experts [24]. The training was also attended by the Pastor.…”
Section: Training Of Church Health Advisors (Chas)mentioning
confidence: 99%
“…All CHHIL sessions focused on nutrition, exercise, behavior change, and setting family health goals. The intervention was formed within a spiritual framework, and faith-based strategies of Fit Body and Soul [22,24] were used to add faith components to the program. CAB members selected the spiritual themes and scripture to frame the three concepts of the program-nutrition, PA, and behavior change.…”
Section: Development Of 8-weeks Group-based Chhil Programmentioning
confidence: 99%
“…Compared to other U.S. populations, African Americans have a higher rate of church membership and have been distinguished as the most religious (Lewis & Taylor, 2009) and giving and receiving the most social support inside the church (Krause, 2016). Studies have shown that African American churches can be an effective setting to promote nutritional education to members (Baruth, Wilcox, Laken, Bopp, & Saunders, 2008; Christie, Watkins, Weerts, Jackson, & Brady, 2010; Dodani, Arora, & Kraemer, 2014). Many African American church leaders have identified the need to address the health issues of their congregation’s members.…”
mentioning
confidence: 99%
“…Many African American church leaders have identified the need to address the health issues of their congregation’s members. Some assign priority to the health and well-being of their members by establishing special committees, as well as ministries that offer health services and health-related programs (Baruth et al, 2008; Dodani et al, 2014). The church has emerged as a vital partner in the effort to reduce health disparities (Austin & Harris, 2011).…”
mentioning
confidence: 99%